Effect of Reimplanting Feedlot Heifers with Ralgro® and/or Synovex-H® - D. LaTourell; Gerry L. Kuhl; C. Drake (Kansas Agricultural Experiment Station Research Reports, 1983)
Implanting heifers initially and mid-way through the finishing period with Ralgro and Synovex-H in any combination produced similar weight gains. Daily gains of cattle implanted with Ralgro + Ralgro, Ralgro + Synovex-H, Synovex-H + Ralgro and Synovex-H + Synovex-H were 3.66, 3.61, 3.66 and 3.75 lbs, respectively.
Keywords: Cattlemen' s Day; 1983; Report of progress (Kansas State University. Agricultural Experiment Station); 427; Beef; Reimplanting; Heifers; Gain